Characteristics of isolation mortars produced with expanded vermiculite and waste expanded polystyrene - Koksal, Fuat; Mutluay, Emrah; Gençel, Osman; Gençel, Osman (Elsevier Sci Ltd, 2020)
Mortar is one of the most important component of cement based composites. Aggregates have also a significant effect on properties of mortars. Generally natural and crushed fine aggregates are used in mortar production for different applications and aims, one of which is energy conservation in buildings and facilities. Vermiculite and waste polystyrene as aggregates in mortar presents an opportunity to reduce the unit weight and the thermal conductivity coefficient that is important for thermal isolation. Five vermiculite+polystyrene/cement ratios, 3, 4, 5, 6 and 7, by volume were used to produce mortars. In each ratio, 100% vermiculite and 100% polystyrene by volume were studied in addition to their combination at 25%, 50% and 75%. Totally, 25 mortars with 4 x 4 x 16 cm were fabricated to investigate physical, mechanical and thermal properties. It was observed that the usage of vermiculite and polystyrene in mortar makes possible the production of mortars with unit weight between 393 and 946 kg/m(3) due to very high porosity up to 67.2%. This is also very important in terms of thermal conductivity which decreases up to 0.09 W/mK. Compressive strength presents a variation between 0.57 and 5.89 MPa. Mortars with vermiculite and polystyrene can be used as a good insulation material where needed. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Lightweight Mortar; Expanded Vermiculite; Expanded Polystyrene (Eps) Waste; Physico-Mechanical Properties; Thermal Conductivity; Recycling